Awareness and understanding of obstructive sleep apnea in Panyananthaphikkhu Chonprathan Medical Center - Jarungjit Kraiwattanapong; Kotchakarn Rattanaarun; Kanittha Choksawad; Katsarin Kittiwannawong; Amonwan Cunteerasup (Songklanakarin Journal of Science and Technology (SJST), 2022)
Awareness of Obstructive sleep apnea (OSA) is increasing worldwide. OSA diagnoses are observed when patients report their sleep problems to their general practitioners. Therefore, the greater the awareness and understanding of OSA in the general population, the more OSA can be detected, to prevent serious consequences of untreated OSA. A cross-sectional study was conducted on 281 cases of population surveyed at Panyananthaphikkhu Chonprathan Medical Center. A statistical analysis of the relationships in the data was pursued. OSA awareness was 81.1%, with the 40-59 year group having the most significant awareness. The perception of OSA symptoms ranged within 55.7-72.7% for sleep apnea, snoring, and daytime sleepiness, while lesser-known symptoms including hypopnea, sudden awakening, choking and gasping for air during sleep was correctly perceived by only 35.2-47.7%. The diseases of reflux, tonsillar hypertrophy, asthma, neurological diseases, and habitual smoking and drinking behaviors, were recognized as possible causes of OSA in only 25-33% of cases. The awareness of OSA can be increased by introducing additional information about lesser-known symptoms of OSA and the diseases associated with OSA to the general public. The recommended main target population is aged 40 – 59 years and of the female gender.